Analisis Tekstual dan Kontekstual Naskah Novel Al-Khubzh Al-Hafiy Karya Muhammad Syukri / Textual And Contextual Analyses of The Novel Text of The Al-Khubzh Al-Hafiy By Muhammad Syukri - Meki Polanda; Putri Nurbaiti (Diwan : Jurnal Bahasa dan Sastra Arab, 2020)
ان الهدف من هذا البحث هو تحليل رواية الخبز الحافي نصياً وسياقياً لمحمد سكري. الطريقة المستخدمة في هذا البحث النوعية الوصفية.  فأما مصدر البيانات هو البيانات الرئيسة هي نص رواية الخبز الحافي ، والبيانات الثانوية هي كتب ومقالات التي تحتوى على تحليل الخطاب النصي والسياقي. وأما نتائج هذا البحث هو تحليل النصي ينقسم إلى جانبين، من الناحية النحوية وجدت عليها شكل المرجع، والاستبدال، والقطع، والاقتران. ومن الناحية المعجمية وجدت فيها التكرار، المرادفات، المتناقض، التجميع، الاختصار، والتكافؤ.  وفي فهم نص رواية الخبز الحافي بتحليل السياقي وجدت فيها المبادئ التي تستخدم كالمراجع منها مبدأ التفسير الشخصي ومبدأ التفسير الموضعي ومبدأ التفسير الزمني ومبدأ التفسير القياس.الكلمات الأساسية: تحليل الخطاب، النصي، السياقي، الخبز الحافي AbstractThis article discusses to analyze the al-Khubzh al-Hafiy novel by Muhammad Syukri textually and contextually. The method used in this article is descriptive qualitative. While the source of data is primary data, which is the text document of the al-Khubzh al-Hafiy novel, and the secondary data are books and articles that discuss textual and contextual discourse analysis. The findings of this article are that textual analysis is divided into two aspects, in which in grammatical terms, it is found in the form of a reference, substitution, ellipsis, and conjunction. And in lexical terms, it is found in the form of repetition, synonymy, antonymy, collocation, hyponym, and equivalence. In the contextual analysis in understanding the text of al-Khubz al-Hafiy novel, there are several principles that are used as a reference, including the principle of personal interpretation, the principle of locational interpretation, the principle of temporal interpretation, and the principle of analogy.